Nonlinear interaction between long inertio-gravity and rossby waves - G. Falkovich; E. Kuznetsov; S. Medvedev (Nonlinear Processes in Geophysics, 1994)
The equations describing the interaction of long inertio-gravity (IG) waves with the Rossby waves are derived. Due to remarkable cancellations, the interaction is shown to be anomalously weak. As a result, an inverse cascade of turbulence produces wave condensate of large amplitude so that wave breaking with front creation can occur.